Efforts To Increase Employee Performance Through Workload Factors, Motivation And Human Resource Management(Msdm) Practices (Study On Employees Of Pt. Bank Negara Indonesia (Bni) Kudus Branch) - Tabitha Ellen Natasya; Diana Aqmala (STIE Amkop Makassar, 2024)
This study analyzes efforts to improve employee performance through workload factors, motivation, and human resource management practices in PT. Bank Negara Indonesia (BNI) Kudus Branch. This study uses a quantitative approach to determine the relationship between variables. This study aims to determine the effect of workload (X1), motivation (X2), and human resource management practices (X3) on employee performance (Y). The data collection method used in this study was distributing questionnaires through Google Forms. The population of this study is all employees who work at PT. Bank Negara Indonesia (BNI) Kudus Branch totaled 67 respondents, and the sample was taken using the Census Sampling Technique. The location of this research is at PT. Bank Negara Indonesia (BNI) Kudus Branch is located at Jl. A. Yani 55 Kel. Panjunan Kec. Kota Kab. Kudus – Central Java. The collected data will then be processed with SPSS Version 25 software analysis. The results of this study show that there is a significant influence of partial workload on employee performance. Subsequent analysis showed that motivation had no partial effect on employee performance. Finally, the results of the analysis show that there is a significant influence between human resource management practices and employee performance. Thus, the performance of employees at PT. Bank Negara Indonesia (BNI) Kudus Branch increased significantly influenced by workload and human resource management practices.